Statistická analýza COVID-19 - Zapoměl, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Diplomová práce se zabývá statistickou analýzou nemoci COVID-19. Práce se věnuje zpracování dat týkajících se nemoci, stanovení a ověření statistických hypotéz, aplikaci po částech lineární regrese, predikce dalšího vývoje nemoci a ověření předpovědi prezentované v médiích. Konkrétní analýzy jsou řešeny pomocí Pythonu.

This thesis deals with the statistical analysis of COVID-19 disease. The thesis focuses on data processing related to the disease, the formulation and verification of statistical hypotheses, the application of piecewise linear regression, the prediction of the further development of the disease, and the verification of predictions presented in the media. Specific analyses are conducted using Python.
Statistical analysis of COVID-19
Keywords: COVID-19; statistické hypotézy; neparametrické testy; diagnostické testy; po částech lineární regrese; Python; COVID-19; statistical hypotheses; non-parametric tests; diagnostic tests; piecewise linear regression; Python